Micronized Purified Flavonoid Fraction in Hemorrhoid Disease: A Systematic Review and Meta-Analysis - Parvez Sheikh (2020)
© 2020, The Author(s). Introduction: Hemorrhoidal disease (HD) is a common and recurrent problem for many adults worldwide. Venoactive drugs, such as micronized purified flavonoid fraction (MPFF; Daflon®), have been used to treat HD and their clinical benefits have been demonstrated in previous meta-analyses of clinical trials. The aim of this study was to evaluate the efficacy of MPFF across the broader spectrum of signs and symptoms following treatment of patients with HD. Methods: We performed a systematic review of the literature to identify randomized clinical trials in which MPFF treatment was compared to placebo or no treatment for acute HD or for relief of symptoms after patients had undergone medical management or a surgical procedure to remove hemorrhoids. The main endpoints investigated were bleeding, pain, pruritus, discharge or leakage, and overall improvement. There was no limit on treatment duration. Results: From 351 unique records retrieved, 11 studies reported in 13 articles were included. On the basis of findings from qualitative analysis, MPFF was reported in most studies to be beneficial in treating bleeding, pain, pruritus, anal discharge/leakage, and tenesmus, and in overall improvement. Quantitative meta-analysis of four studies indicated that MPFF treatment provided significant benefits for bleeding (odds ratio [OR] 0.082, 95% confidence interval [CI] 0.027–0.250; P < 0.001), discharge/leakage (OR 0.12, 95% CI 0.04–0.42; P < 0.001), and overall improvement according to patients (OR 5.25, 95% CI 2.58–10.68; P < 0.001) and investigators (OR 5.51, 95% CI 2.76–11.0; P < 0.001). MPFF also tended to decrease pain (OR 0.11, 95% CI 0.01–1.11; P = 0.06). Conclusion: Taken together, these results suggest that MPFF treatment can improve the most important signs and symptoms of HD.